Корозійно-електрохімічні властивості метал-оксидних і композитних систем - Ведь, Марина Віталіївна; Сахненко, Микола Дмитрович; Овчаренко, Ольга Олександрівна; Зюбанова, Світлана Іванівна; Горохівський, Андрій Сергійович; Каракуркчі, Ганна Володимирівна; Славкова, Марина (Фізико-механічний інститут ім. Г. В. Карпенка НАН України, 2016)
The results of the research aimed to establish a patterns of electrochemical synthesis coatings both mono- and doped oxides in the modes of plasma electrolytic oxidation (PEO), as well as composite systems of metal matrix reinforced with an oxide phasearepresented. The influence of external conditions and internal factors on the structure, element composition, morphology and operating properties of the obtained materials is analyzed. It was established that the composition, surfacemorphology and functional properties of oxide coatings on titanium and aluminum alloys depend on the composition of electrolytes andoxidation mode. It is proved the possibility obtaining multicomponent oxide coatings with high adhesionin one-stageusing PEO. Doping of a titanium matrix with zirconium and zinc oxides allows to raise essentially their photocatalytic properties both due to the formation of large globules on the smoothed surface of mixed oxide systems Ti/TiOₓ, ZnO and Ti/TiOₓ, ZrO₂ containing dopant to 3 at.% in terms of metal, as well as by the synergetic effect. Increased corrosion and abrasion resistance for PEO systems Ti/TiOₓ, ZrO₂ is caused by chemical properties of the dopant and uniform micro globular surface morphology. It is found that mixed oxides coatings systems Al/Al₂O₃, CoOₓ and Al/Al₂O₃, MnOₓ, CoOₓ as promising materials for heterogeneous catalysis can be prepared by electrochemical technology on metal substrates in PEO mode. It was noted increase of their corrosion and abrasion resistance in comparison with Al/Al₂O₃ caused by homogenization of the surface layer and the formation of smooth micro globular structure. The system Al/Al₂O₃, MnOₓ, CoOₓ identified the highest catalytic properties with the total content of the dopants to 6 at.% in a bench test of the diesel engine in the forced modes reduces fuel consumption by 1-3%, decreases NOₓ emissions and substantially improves environmental performance. Composite coatings based on electrochemical metal copper and nickel matrices reinforced by 1,5 at.% nano-sized particles of the hardening phase Al₂O₃, have a significantly higher physical and mechanical properties – micro-hardness, tensile strength and yield strength compared with monometallic materials. It is found that one of the factors contributing to almost doubling of these characteristics is a decrease in the grain size which also improves corrosion resistance of the coatings in spite of their heterogeneity.
Corrosion and electrochemical properties of the metal-oxide and composite systems
Keywords: композитні електрохімічні покриви; метод ПЕО; імпедансометрія; нейтралізація токсидів; aluminium alloys; titanium alloys; oxide coatings; plasma electrolytic oxidation; composite coatings; reinforced phase; surface morphology